Restoring the fertility of Africa's degraded lands: the process approach - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The scale of the problem may be subject to debate - but there is no doubting that land degradation is one of the most serious threats to food production over much of Africa. In extreme cases land may be so badly degraded that it is abandoned by...